1973
DOI: 10.1111/j.1471-4159.1973.tb07532.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Age, Growth Retardation and Asphyxia on Ascorbic Acid Concentrations in Developing Brain

Abstract: Abstract— The concentration of ascorbic acid in whole rat brain during the first week of postnatal life was up to 100 per cent higher than in adult animals. A progressive fall in concentration occurred between 4 and 30 days of age. Corresponding changes did not occur in liver and adrenal gland, two other organs rich in ascorbic acid. Rats subjected to growth retardation during the fetal and suckling periods had, at 25 days of age, levels of ascorbic acid in the cerebellum and brainstem significantly higher tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
1

Year Published

1974
1974
2014
2014

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(22 citation statements)
references
References 13 publications
3
18
1
Order By: Relevance
“…USA 88 (1991) 11161 against ischemic injury, since depletion of brain GSH with buthionine sulfoximine, a selective inhibitor for -t-glutamylcysteine synthetase, increased postischemic infarct size and edema. As in other tissues, ascorbic acid exists almost exclusively in its reduced form in brain (>99%) (2,8,33). It has also been reported that AH2 decreases significantly following cerebral ischemia and head injury.…”
Section: Methodsmentioning
confidence: 96%
“…USA 88 (1991) 11161 against ischemic injury, since depletion of brain GSH with buthionine sulfoximine, a selective inhibitor for -t-glutamylcysteine synthetase, increased postischemic infarct size and edema. As in other tissues, ascorbic acid exists almost exclusively in its reduced form in brain (>99%) (2,8,33). It has also been reported that AH2 decreases significantly following cerebral ischemia and head injury.…”
Section: Methodsmentioning
confidence: 96%
“…Data are mean 2~ SEM; OB olfactory bulb, CTX cortex, DVR dorsal ventricular ridge, CB cerebellum, OL optic lobe, BS brainstem, SC spinal cord, ON optic nerve, HP hippocampus, SC superior colliculus (modified from Rice et al, 1995). 1992), have a key role in preventing oxidative damage during reoxygenation after a hypoxic dive. Intriguingly, ascorbate is also high in neonatal rats (Adlard et al, 1973;Allison and Stewart, 1973;Rice and Russo-Menna, 1998), which also have greater tolerance of anoxia than do adults (Kabat, 1940;Xia et al, 1992). As di,;cussed more fully below, high brain ascorbate levels in neonatal rats reflect the predominance of h!igh-ascorbate neurons in rat CNS before the later proliferation of low-ascorbate glial cells (Rice and RussoMenna, 1998).…”
Section: Ascorbate a N D Gsh As Antioxidantsmentioning
confidence: 94%
“…It is believed that in fetal and newborn animals the levels are somewhat higher (24)(25)(26). Thus, aqueous brain extracts contain sufficient amounts of ascorbic acid to account for their ability to induce AcChoR accumulation in vitro.…”
Section: Methodsmentioning
confidence: 99%